TO STUDY THE PROBABILITY OF TOXIC AND LETHAL EFFECTS OF PYRIDINE ADMIXTURE IN MEDICINAL PRODUCTS - Волкова Aллa Андрeeвнa; Калекин Рoмaн Aнaтoльевич; Орлова, Алевтина Михайловна (Medicine in Kuzbass, 2024)
Pyridine is included in the composition of some drugs as an impurity, as it is used in the synthesis of pharmaceutical production. Pyridine exhibits toxic properties on the human body. Due to its high toxicity, pyridine belongs to the second hazard class, which corresponds to a highly dangerous substance. The influence on the fact of poisoning and death due to the presence of this impurity has been established. A case from practice is described, which allows an objective assessment of the effect of pyridine on the body, which will facilitate the approach to research in the production of forensic medical examination. The aim of the research was to determine the possible effect of the presence of pyridine in the dosage form of ceftazidime on the fact of clinical death after infusion therapy to the patient. Materials and methods. A method of high-performance liquid chromatography to establish the quantitative content of pyridine in the dosage form of ceftazidime and a retrospective analysis of the patient’s medical documentation. The toxic effect of pyridine contained in ceftazidime formed over a 24-hour period can have toxicity on the human body, therefore, the daily administration of pyridine was 18 mg. Results. However, after theoretical recalculation to the injection route of administration, the lethal dose of pyridine with the injection route of administration is about 3 g for the average statistical person, that is, the daily dose of pyridine is more than 100 times less than the lethal dose. Conclusion. It was determined that when prescribing a course of administration with a drug, the amount of the injected ceftazidime drug cannot cause clinical death due to the presence of pyridine admixture in it, which was insignificant for the human body.